PENDAMPINGAN BAGI GURU DI SEKOLAH INDONESIA BANGKOK (SIB) DALAM MENINGKATKAN PEMBELAJARAN LITERASI - Widyaswari, Monica; Indrawati, Delia; Khusumadewi, Ari; Cindy, Agustin Hanivia; Pramana, Atan (Jurnal Pengabdian Masyarakat Indonesia, 2024)
Literacy is the activity of reading, understanding, and applying information that is an essential foundation for children in their golden age. The Indonesian School of Bangkok faces challenges in literacy in early grades that affect students' abilities related to reading, writing, and understanding texts. Teachers/educators must use a comprehensive and progressive approach in teaching literacy to foster children's reading interests and critical thinking skills. The mentoring program carried out aims to train early-grade teachers in literacy instruction. The mentoring methods included identifying needs, focus group discussions (FGDs) using a share and care approach, practice, and evaluation. The results showed significance, with an average score above 80 for aspects such as participant numbers, the conditioning of the support process, the competence of the resource persons, and the presentation of materials. Participants demonstrated improved understanding and readiness to apply new techniques. Positive feedback suggests that support was highly relevant and applicable, enhancing literacy teaching abilities at the Indonesian School of Bangkok. Recommendations include integrating more technology and interactive methods to enrich student's learning experiences and encouraging teacher collaboration to strengthen the implementation of techniques learned in the classroom.